The Role of Christian Religious Education in the Recovery of Mental Disorders - Yunus Tan (International Journal Labs, 2022)
Background: Christian religious education is not only limited to scientific learning but also practiced in everyday life, one of which is in the recovery of mental disorders. Objective: This study aims to determine the role of Christian religious education in the recovery of mental disorders. Method: This research uses qualitative research methods with a descriptive approach, while data collection techniques are carried out with literature studies through the exploration of journals, books, and other information relevant to the study. Results: The results showed that the role of Christian religious education in the recovery of mental disorders is as a guide to teach the meaning of life, to keep away those who trigger problems, to bring good hope, and to bring tranquility. Conclusion: The results showed that the role of Christian religious education in the recovery of mental disorders is as a guide to teach the meaning of life, to keep away those who trigger problems, to bring good hope, and to bring tranquility.